Determination of Physical and Chemical Properties of the Soils Under Different Land Managements - Durak, A.; buyukguner, E.; Dogan, H.M. (Asian Journal of Chemistry, 2010)
This study aimed to determine the effects of different land management systems on the physical and chemical properties of soil. The study was conducted on a cultivated land, forest land and orchard adjacent to each other on the same topographic position at Tokat Rural Research Institute. With this aim, 10 soil samples were taken randomly from 0-30 and 30-60 cm depths of each land management area. The physical (field capacity, wilting point water content, soil texture, hydraulic conductivity, bulk density) and chemical (organic matter, CaCO3 content, pH, EC, cation exchange capacity, nitrogen, phosphorus, exchangeable sodium, potassium, calcium, magnesium) properties of the soil samples were examined and the spatial variability of the soil properties were mapped by using geographic information systems (GIS). The statistical evaluation indicated that all topsoil (0-30 cm) properties except phosphorus, silt and exchangeable sodium showed statistically significant differences (p < 0.05) at three land management systems. Whereas, all subsoil (30-60 cm) properties but silt, exchangeable sodium and hydraulic conductivity revaled statistically significant differences (p < 0.05) at three land management systems. The study concluded that the properties of soil change through land management and they should be done based on the physical and chemical properties of the lands following their classification for soil quality and environmental protection.